Cost effective and Monodispersed Zinc Oxide Nanoparticles Synthesis and their Characterization - Rohit Saraf (International Journal of Advances in Applied Sciences, 2013)
Zinc Oxide (ZnO) Nanoparticles are most widely used in the field of Biotechnology and Nanoelectronics due to their good transparency, high electron mobility, strong room-temperature luminescence and nontoxic. Due to their increasing demand, highly specified and monodispersed nanoparticles formation is a revolutionary field. Here ZnO nanoparticles are prepared by modified sol-gel method and are characterized using UV-Vis Absorption Spectroscopy, X-ray Diffraction and Scanning Electron Microscopy (SEM). Modified sol-gel mediated ZnO nanoparticles are proved to synthesize the highly stable, monodispersed and cost effective nanoparticles. The results are quite appreciable and wide band gap- long range ordered ZnO nanoparticles are obtained than the conventional route.